تأثير التدريب الذهني المصحوب بإيقاعات موسيقية في تعلم بعض المهارات الأساسية بتنس الطاولة للطلاب والاحتفاظ بها - غفور, توانا وهبي; محمد, شيلان حسين (Sulaimani Journal for Humanities, 2021)
The purpose of the current study is to identify the effect of indirect mental training accompanied by musical rhythms between the pre-test and post-test in learning some basic skills of table tennis (front and back straight stroke and dispatch) for students. The study also aims at investigating the differences between the research groups in remote usability testing as well as examining the differences in the arithmetic circles between three research groups. The researchers used the experimental method, and purposive sampling is used to recruit the participants of the study who are students of the second academic year at the Faculty of Physical Education and Sports Science at the University of Sulaymaniyah (N=30). The participants were divided into three equal groups, two groups of which are experimental and the other is control. The educational curriculum is used for the pre-test and post-test which consists of 12 units per group, with two educational units per week, and the time of indirect mental training 5 minutes per skill. The researchers reached a conclusion that the use of indirect mental training accompanied by musical rhythms had a positive effect in learning some basic skills of table tennis for students, and we also reached the superiority of the second experimental group (indirect mental training with loud musical rhythms) over other groups in learning The front and back straight striking skills, while the first experimental group (indirect mental training accompanied by calm musical rhythms) outperforms the other groups in the transmission skill. The researchers recommended that the need to use indirect mental training during the learning process for some basic skills of table tennis for students, and the need to include music within the educational units for student learning in order to speed learning and invest time and effort.
Keywords: (mental training; musical rhythms; basic skills; table tennis; Retention)